An Analysis Of Work Motivation, Supervision, And Work Commitment On Employee Work Discipline At The Office Of The Confederation Of All Indonesian Workers - Fajar, Muhammad Halim; Yanti, Eli Delvi; Sebayang, Saimara A.M. (Journal of Management, Economic, and Accounting, 2026)
This study aims to examine the influence of work motivation, supervision, and employee commitment on work discipline at the Confederation of Indonesian Trade Unions (Konfederasi Serikat Pekerja Seluruh Indonesia). The research adopts a quantitative approach with a causal asositif design to analyze the relationships among variables. The entire population, consisting of 48 employees, was included as research respondents. Data were collected through questionnaires and analyzed using multiple linear regression techniques. The results indicate that: (1) work motivation (X1) has a significant and positive effect on employee discipline (Y); (2) supervision (X2) also significantly enhances employee discipline (Y); (3) employee work commitment (X3) exerts a significant positive influence on work discipline (Y); and (4) simultaneously, work motivation, supervision, and employee commitment affect employee discipline, contributing 85.1% to the explained varianc e, while the remaining 14.9% is influenced by other factors beyond the scope of this study. These findings suggest that higher levels of motivation, effective supervision, and stronger commitment contribute to improved employee discipline within the organization.